Deformation mechanism in NiAl single crystals at low temperatures. (February 2015) - Butt, M.Z.; Ali, Dilawar
Abstract: Available data on the temperature dependence of yield stress and of associated activation volume of high-purity NiAl single crystals between 76 and 205 K have been analyzed within the framework of a solid-solution hardening model, which is based on the concept of depinning of an edge-dislocation segment from several randomly dispersed, isolated, point defects simultaneously. The vacancies in NiAl single crystals act as point-defect obstacles to the stress-assisted thermally-activated glide of edge dislocations, and their concentration is estimated as about 10 at.%. The product of yield stress and associated activation volume (≈0.146 eV) is found to be independent of temperature and yield stress, as envisaged in the model. Highlights: Yield stress of NiAl decreases with the increase in temperature from 75 to 205 K. Activation volume increases with the increase in temperature from 75 to 205 K. Product of yield stress and activation volume is independent of temperature. Observations are explicable by Butt–Feltham model of solid-solution hardening. An edge-dislocation segment breaks away from several vacancies simultaneously.